Metal–Organic Framework Decorated Cuprous Oxide Nanowires for Long‐lived Charges Applied in Selective Photocatalytic CO2 Reduction to CH4 - Wu, Hao; Kong, Xin Ying; Wen, Xiaoming; Chai, Siang‐Piao; Lovell, Emma C.; Tang, Junwang; Ng, Yun Hau (Angewandte Chemie International Edition, 2021)
Improving the stability of cuprous oxide (Cu2O) is imperative to its practical applications in artificial photosynthesis. In this work, Cu2O nanowires are encapsulated by metal–organic frameworks (MOFs) of Cu3(BTC)2 (BTC=1,3,5‐benzene tricarboxylate) using a surfactant‐free method. Such MOFs not only suppress the water vapor‐induced corrosion of Cu2O but also facilitate charge separation and CO2 uptake, thus resulting in a nanocomposite representing 1.9 times improved activity and stability for selective photocatalytic CO2 reduction into CH4 under mild reaction conditions. Furthermore, direct transfer of photogenerated electrons from the conduction band of Cu2O to the LUMO level of non‐excited Cu3(BTC)2 has been evidenced by time‐resolved photoluminescence. This work proposes an effective strategy for CO2 conversion by a synergy of charge separation and CO2 adsorption, leading to the enhanced photocatalytic reaction when MOFs are integrated with metal oxide photocatalyst. Cu2O nanowires are decorated with Cu3(BTC)2 by a surfactant‐free method. The Cu2O@Cu3(BTC)2 core–shell structure offers enlarged active surfaces and prolonged lifetime of separated electrons for CO2 reduction into CH4, exhibiting enhanced photocatalytic activity and stability compared to the bare Cu2O.